Advancements in pH-Responsive nanoparticles for osteoarthritis treatment: Opportunities and challenges - Liao, Shuai; Jia, Shicheng; Yue, Yaohang; Zeng, Hui; Lin, Jianjin; Liu, Peng (Frontiers in Bioengineering and Biotechnology, 2024)
Osteoarthritis (OA) is a degenerative disease linked to aging and obesity. The global aging population has led to an increasing number of OA patients, imposing a significant economic burden on society. Traditional drugs treatment methods often fail to achieve satisfactory outcomes. With the rapid advancement of nanomaterial delivery systems, numerous studies have focused on utilizing nanomaterials as carriers to achieve efficient OA treatment by effectively loading and delivering bioactive ingredients (e.g., drugs, nucleic acids) tailored to the unique pathological conditions, such as the weakly acidic microenvironment of synovial fluid in OA patients. This review highlights the latest advancements in the use of pH-responsive nanoparticles for OA treatment, emphasizing the principle of targeted drug delivery leveraging the acidic microenvironment of inflamed joints. It further discusses the composition, synthesis, response mechanism, target selection, application, and recent research findings of nanoparticles, while also addressing the challenges and future directions in this promising field.